Elevated UV photon fluxes minimally affected cannabinoid concentration in a high-CBD cultivar - Westmoreland, F. Mitchell; Kusuma, Paul; Bugbee, Bruce (Frontiers in Plant Science, 2023)
Ultraviolet photons (UV; less than 400 nm) can damage critical biochemical processes. Plants synthesize photo-protective pigments that absorb UV to minimize damage. Cannabinoids absorb UV, so increased UV has the potential to increase cannabinoid synthesis. Studies in the 1980's provided some evidence for this hypothesis in low-cannabinoid cultivars, but recent studies did not find an increase in cannabinoid synthesis with increasing UV in high-cannabinoid cultivars. These studies used low UV photon fluxes, so we examined the effect of higher UV photon fluxes. We used fluorescent UV lights with 55% UV-B (280 to 314 nm) and 45% UV-A (315 to 399 nm). Treatments began three weeks after the start of short days and continued for five weeks until harvest. Established weighting factors were used to calculate the daily biologically effective UV photon flux integral (UV-PFDBE; 280 to 399 nm). Daily UV-PFDBE levels were 0, 0.02, 0.05, and 0.11 mol m -2 d -1 with a background daily light integral (DLI) of 30 mol m -2 d -1 from white+red LEDs. These levels provided a ratio of daily UV-PFDBE to DLI of 41 to 218% of summer sunlight in the field. Cannabinoid concentration was unaffected by UV. Fv/Fm and flower yield were reduced only in the highest UV treatment. These data support recent literature and lead us to conclude that an elevated flux of UV photons is not an effective approach to increase cannabinoid concentration in high-cannabinoid cultivars.